Integrated Virtual Exercise for Older Adults in Remote Patient Monitoring Program: A Feasibility Study - Jake Tran; Reena Ahluwalia; Danielle Kilby-Lechman; Bonaventure A. Egbujie (Journal of Primary Care & Community Health)
Objectives: This study tested the feasibility of integrating a virtually facilitated exercise intervention into routine RPM program for older adults to establish its acceptability and patients’ satisfaction. Methods: We performed a retrospective analysis of data curated from a population-based virtual exercise intervention for older adults receiving RPM in Ontario, Canada. Results: A total of 16 patients participated in at least 1 exercise class, 64% were females, with mean (SD) age of 76 (±10) years. Overall, 100% of participants were “very satisfied” with the program, 81.3% (13) agreed/strongly agreed that the program “motivated them to move,” while 100% (16) agreed/strongly agreed that participating in the intervention has improved their physical endurance. Attendance to the virtual classes were relatively good with patients attending more than 60% of scheduled classes per session. Comorbidity had a strong effect on attendance, with the presence of each additional chronic condition associated with a 15.8% decline in attendance rate ( P  = .005) over time Conclusion: Integrating a virtually facilitated exercise program into routine RPM program for older adults is feasible, acceptable, as well as safe. Larger studies are required to establish efficacy of the intervention in improve health outcomes.